Digital Literacy of LAZIS Syuhada Yogyakarta in Building Public Awareness through Philanthropy Product Branding - Kurniawan (International Journal of Applied Educational Research (IJAER), 2024)
This research describes the literacy of LAZIS Syuhada Yogyakarta in branding activities for the economic empowerment of the poor through the utilization of Information and Communication Technology online. One of the literacy efforts made by LAZIS Syuhada is branding the economic empowerment products of the poor to promote Islamic philanthropy and attract donors to donate. Branding the product is expected to build public awareness and knowledge (literacy) about LAZIS Syuhada's philanthropic activities, especially through social media. Social media is used by LAZIS Syuhada to increase public literacy of the branded products through information and promotions that are disseminated, so as to attract donations. This study contributes to understanding LAZIS Syuhada's literacy strategy in branding economic empowerment products as a form of philanthropic promotion so that people know and get involved in it. This study uses library research and descriptive analytics. The results of the study are expected to contribute to understanding LAZIS Syuhada's literacy strategy in its philanthropic product branding activities.